Implementasi CI/CD Pada Microservices Untuk Meningkatkan Availability Pada Pemrosesan Big Data - Kompiang Gede Sukadharma; I Putu Gede Hendra Suputra (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2024)
Big Data Processing needed a reliable system that not let the data loss. But sometimes we need to make the system down for a while because we need to push the newest changes of the system. The automation will help us achieve that. Continuous Integration and Continuous Deployment help us to reduce the downtime and increase the availability of the system. Thus, the implication will be led to reduce of data loss. This research focusses on the implementation of CI/CD Pipeline on single-point-of-failure service on Microservices Architecture. This research use Load-Testing to measure data loss on certain amount of time. The result on this research show that implementing CI/CD Pipeline on the Microservices that we made, make the down time will be less than 45 Second with 20 Virtual user who send the data.